EDUCATING BORDER DWELLERS TO PROMOTE PEACE AND SECURITY IN AN ELECTORAL PROCESS: PERCEPTION OF COMMUNITY MEMBERS’ - Muhinat, Bello Bolanle (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2020)
This study examined the perception of border community members on educating border dwellers so as to promote peace and security in an electoral process in Nigeria. The study adopted a descriptive survey design, with a target population of This study examined the perception of border community members on educating border dwellers so as to promote peace and security in an electoral process in Nigeria. The study adopted a descriptive survey design, with a target population of Zamfara state’s Zurmi Local Government Areas border communities of Gurbin Bore. Researcher’s designed questionnaire with psychometric properties of content validity of 0.61 and a reliability index of 0.87 was used to elicit the needed data from the respondents. A multistage sampling technique was used to sample 384 respondents. The research questions and hypotheses were analyzed using mean score and t-test. The finding revealed that all the community members perceive educating them as a welcome development that would help in breeding youth that is needed in an electoral process. It was thus, recommended among others that, the government should provide qualitative education for people residing in the international border areas